(untitled) (Revista de Investigaciones Universidad del Quindío, 2012)
This paper contains a theoretical introduction about the Direct Sequence Spread Spectrum (DSSS) transmis-sion technique, and the advantages obtained by modifying its configuration parameters. An overview about the short range 2.4 GHz DSSS-based wireless communication system is presented, and its implementation in the Programmable Radio-on-Chip (PRoC) devices from Cypress Semiconductor Corp. A test plan was designed to evaluate and analyze the physical level performance of the system in order to obtain the received power measurements and number of bit errors in the received information, at different data transmission rates in three different scenarios: outdoor, indoor and interference-scenario. The obtained results allowed realize a comparative analysis to determine the behavior of the communication system under different ope-rating conditions and in different scenarios.